An investigation into folate deficiency in healthy underprivileged infants with special emphasis on the interpretation of the Figlu test after oral histidine - Friedman, Ruth (Department of Paediatrics and Child Health, 2020)
In South Africa, as: in other countries with a large underprivileged population group, the problem of malnutrition and its- associations and complications assumes considerable importance. Until the socioeconomic problems involved are solved, attention must be directed to early diagnosis, treatment and prophylaxis of malnutrition and its associations. At the Red Cross Children's Hospital, Cape Town, a considerable percentage of admissions are for marasmus and kwashiorkor. Anemia is a frequent association, (Walt, I.959) sometimes contributing to the mortality (Walt, Holman and Naidoo, 1957).